The empirics of the median voter: Democracy, redistribution and the role of the middle class - Francesco Scervini (Luxembourg Income Study (LIS), 2009)
The paper investigates the effectiveness of the median voter as a decisive agent in the process of redistribution. According to the previous literature, it tests several assumptions finding interesting results: The positive relation between inequality and redistribution is confirmed, but the median voter theorem seems not to be the driving force of this mechanism. Even if some results support the median voter hypotheses, many others go in the opposite direction. Moreover, results are in support of the presence of a political bias toward rich classes, particularly in non established democracies. Finally, the elasticity of redistribution to poor classes to their income has decreased over the last decade, suggesting a reduction of the policies in support of low income individuals.
Keywords: D31; D72; H42; 330; Income distribution; Cash redistribution; Political process; Median voter theorem; Time invariant unobserved heterogeneity; Medianwähler-Modell; Mittelschicht; Einkommensumverteilung; Einkommensverteilung; Gini-Koeffizient; Welt